1989
DOI: 10.1042/cs0760479
|View full text |Cite
|
Sign up to set email alerts
|

Regional and time-dependent effects of inflammatory mediators on airway microvascular permeability in the guinea pig

Abstract: 1. Airway oedema resulting from increased microvascular permeability is a characteristic pathological finding of asthma. The regional effects of putative mediators involved in asthma on airway microvascular permeability have been studied. 2. The effects of histamine, leukotriene (LT) D4 and platelet-activating factor (PAF) on microvascular permeability in the nasal mucosa, larynx, trachea, main bronchi and intrapulmonary airways of the guinea pig were assessed by measuring the extravasation of intravenously ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 0 publications
1
21
1
1
Order By: Relevance
“…There are several reports that the cys-LTs increase microvascular permeability in guinea pig airways (Woodward et al, 1983a,b;Evans et al, 1989;Bochnowicz and Underwood, 1995); the mechanism may involve contraction of endothelial cells resulting in gaps in the endothelium of venules (Joris et al, 1987). This influence of the cys-LTs, which appeared to involve both direct and indirect pathways, was inhibited by either FPL 55712 (Woodward et al, 1983a) or pranlukast Bochnowicz and Underwood, 1995) indicating that a CysLT 1 receptor was involved.…”
Section: Diverse Effects Of Cysteinyl-leukotrienesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reports that the cys-LTs increase microvascular permeability in guinea pig airways (Woodward et al, 1983a,b;Evans et al, 1989;Bochnowicz and Underwood, 1995); the mechanism may involve contraction of endothelial cells resulting in gaps in the endothelium of venules (Joris et al, 1987). This influence of the cys-LTs, which appeared to involve both direct and indirect pathways, was inhibited by either FPL 55712 (Woodward et al, 1983a) or pranlukast Bochnowicz and Underwood, 1995) indicating that a CysLT 1 receptor was involved.…”
Section: Diverse Effects Of Cysteinyl-leukotrienesmentioning
confidence: 99%
“…Although LXA 4 and LXB 4 are similar in structure, these mediators display biological activities that are quite distinct. LXA 4 interactions with neutrophils involves binding sites that are not rec- Dihydroxy-leukotrienes (LTB 4 ) Leukocyte activation Bray et al, 1980;Ford-Hutchinson et al, 1980;Goetzl and Picket, 1980;Serhan et al, 1982 Cytokine secretion Luscinskas et al, 1990;Rola-Pleszczynski et al, 1993 Nuclear transcription (PPAR␣) Devchand et al, 1996IgE synthesis Odlander et al, 1988Yamaoki et al, 1994 Cysteinyl-leukotrienes (LTC 4 , LTD 4 , LTE 4 ) Bronchospasm Drazen et al, 1980;Weiss et al, 1982;Barnes et al, 1984;Jones et al, 1985;Davidson et al, 1987;Smith et al, 1993Plasma exudation Woodward et al, 1983Evans et al, 1985;Obata et al, 1992Vasoconstriction Smedegard et al, 1982Filep et al, 1985;Garcia et al, 1987;Evans et al, 1989Vasodilation Secrest et al, 1985Sakuma and Levi, 1988;Lawson et al, 1989;Pawloski and Chapwick, 1993b;Ortiz et al, 1995 Eosinophil recruitment Foster andChan, 1991;Laitinen et al, 1993;Smith et al, 1993;Spada et al, 1994;Underwood et al, 1996Cardiodepression Levi et al, 1980Burke et al, 1982;Bittl et al, 1985;Roth et al, 1985 Smooth muscle proliferation Wang et al, 1993;…”
Section: Nomenclature For Leukotriene Receptorsmentioning
confidence: 99%
“…Cysteinly leukotrienes (LTs) are now well recognized as inducing potent constriction of the human bronchi [1], in flammation in the airways [2,3], and increasing human bronchial hyperresponsiveness in asthmatics [4], These re sults suggest that LTs could play an essential role in the pathogenesis of bronchial asthma. Pranlukast, a selective LTC4/D 4/E4 receptor antagonist, developed in Japan, has been in clinical use since June 1995 for the treatment of bronchial asthma, and its clinical usefulness is now being K ARfiFR © 1997 S. Karger AG, Basel C l \ | 0lg 2438/97/1141 0097S 12.00/0 E-Mail kargere« karger.ch Fax +41 61 306 12 34 This article is also accessible online at: http://www.karger.ch http://BioMedNet.com/karger evaluated by physicians.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of inflammatory mediators on airway vascular permeability is regionally dependent (Evans et al, 1989), and indeed we observed that a significant amount of plasma extravasation was induced by a lower dose of PAF (500 ng kg-') in the larynx and trachea compared with smaller airways. We also observed that adrenalectomy potentiates PAF-induced increase in vascular permeability in the larynx, trachea, main bronchi, but not in the intrapulmonary airways.…”
Section: Discussionmentioning
confidence: 73%